2002
DOI: 10.1182/blood-2002-02-0651
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow transplantation: cure for familial Mediterranean fever

Abstract: We describe data on a 7-year-old girl with congenital dyserythropoietic anemia (CDA), who also had familial Mediterranean fever (FMF). Repeated transfusions required since the age of 6 months to treat her CDA led to iron overload and a persistently high ferritin level. Her relapsing FMF made effective iron chelation therapy very difficult. Consequently, at the age of 4 years, she underwent allogeneic, sibling bone marrow transplantation (BMT). During conditioning for her BMT, symptoms of FMF, including splenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Therefore, the concept that bone marrow transplantation has no role in the therapeutic approach to patients with FMF is shared by all clinicians dealing with FMF. Nevertheless, an interesting case report underscoring the curative potential of this therapeutic modality therapy has been reported by Milledge et al [ 40 ]. They reported on a 7-year-old girl with congenital dyserythropoietic anemia (CDA) who also had FMF.…”
Section: Allogeneic Bone Marrow Transplantationmentioning
confidence: 89%
“…Therefore, the concept that bone marrow transplantation has no role in the therapeutic approach to patients with FMF is shared by all clinicians dealing with FMF. Nevertheless, an interesting case report underscoring the curative potential of this therapeutic modality therapy has been reported by Milledge et al [ 40 ]. They reported on a 7-year-old girl with congenital dyserythropoietic anemia (CDA) who also had FMF.…”
Section: Allogeneic Bone Marrow Transplantationmentioning
confidence: 89%
“…In such patients, several adjunctive approaches are under investigation, including subcutaneous interferon-a [125,126 • ,127 • ] and biologic therapies aimed at TNF [128 • ] or interleukin-1b. Allogeneic bone marrow transplantation has recently been proposed as a treatment for refractory FMF [129], based on the predominant expression of MEFV in leukocytes [5]. Although it is possible that this approach could be effective, in nearly all cases other options exist, and the risks outweigh the potential benefits [130].…”
Section: Treatmentmentioning
confidence: 99%
“…Allogeneic bone marrow transplantation has also been shown to be effective in the prevention of FMF attacks (9). Several recent reports have demonstrated that the anti-tumor necrosis factor (TNF)-α monoclonal antibody, infliximab, reduces the frequency of FMF attacks in Spanish and Turkish patients (10,11 …”
Section: Familial Mediterranean Fever (Fmf) Is An Autoinflammatory DImentioning
confidence: 99%